2022
DOI: 10.1186/s13014-022-02051-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic contrast-enhanced computed tomography generation using a deep convolutional neural network for cardiac substructure delineation in breast cancer radiation therapy: a feasibility study

Abstract: Background Adjuvant radiation therapy improves the overall survival and loco-regional control in patients with breast cancer. However, radiation-induced heart disease, which occurs after treatment from incidental radiation exposure to the cardiac organ, is an emerging challenge. This study aimed to generate synthetic contrast-enhanced computed tomography (SCECT) from non-contrast CT (NCT) using deep learning (DL) and investigate its role in contouring cardiac substructures. We also aimed to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The deep convolutional neural network could also generate synthetic contrast-enhanced CT images from non-enhanced contrast CT images, and then be used to contour cardiac substructures. Chun et al (77) applied this method to the automatic segmentation of cardiac substructures in patients with breast cancer undergoing radiotherapy and proved the feasibility of this method.…”
Section: Automatic Segmentation Of Cardiac Substructures Based On Dee...mentioning
confidence: 99%
“…The deep convolutional neural network could also generate synthetic contrast-enhanced CT images from non-enhanced contrast CT images, and then be used to contour cardiac substructures. Chun et al (77) applied this method to the automatic segmentation of cardiac substructures in patients with breast cancer undergoing radiotherapy and proved the feasibility of this method.…”
Section: Automatic Segmentation Of Cardiac Substructures Based On Dee...mentioning
confidence: 99%
“…In recent studies, AI-based approaches have demonstrated the possibility of reducing the amount of gadolinium-based contrast agents (GBCAs) in magnetic resonance imaging (MRI) [1][2][3][4][5][6][7][8] and iodine-based contrast media (ICM) in computed tomography (CT). [9][10][11][12][13][14] For both modalities, the amount of contrast agent respectively can be technically optimized in completely different ways, for example, by means of applications for the optimization of the radiation spectrum such as CareKV 15 for CT or by means of sequence, 16 molecule relaxivity, 17,18 and acquisition time optimization for MRI. 19 While at the same time, the techniques of AI-based contrast optimization and the issues regarding contrast reduction are similar.…”
mentioning
confidence: 99%
“…Furthermore, AI-based methods for virtual contrast enhancement 11,[24][25][26][27][28][29][30] could raise the diagnostic quality of noncontrast data in situations where contrast agent administration is contraindicated, such as in patients with severe allergies or, in case of CT imaging, patients with severe hyperthyroidism. 31 Last but not least, new fields of image contrast modification promise to produce more than a normal contrast agent dose and may further improve the radiologist's sensitivity in detecting small lesions.…”
mentioning
confidence: 99%
See 2 more Smart Citations